The Influence of Social Media Interactions on Consumer Behavior in Influencer vs. User-Generated Destination Content: The Role of Source and Content Factors - Listiawardany, Elmira; Astuti, Rifelly Dewi (ASEAN Marketing Journal, 2025)
Based on Service Dominant Logic, Value Co-Creation, and the Information Adoption Model, this research model examines the influence of Social Media Interactions on destination content on Visit Intention and Behavioral Engagement, involving Source Credibility, Homophily, and Content Quality as mediators in this relationship. To provide more specific implications, this study also compares how the model applies to two different types of content, namely influencer content and user-generated content (UGC). This research uses a survei questionnaire method and obtained 313 samples that meet this research criteria, which are those who located in Indonesia, age 17 to 43, using social media, and exposed to destination content in the last 1 month. Based on analysis using SmartPLS software, this study found that Social Media Interactions on destination content positively influence consumers' interest in visiting the destination (Visit Intention) and trigger their engagement behavior with the content (Behavioral Engagement). Homophily with the content source and the quality of the destination content (Content Quality) were also proven to play intermediary roles in this relationship. Additionally, the findings of this study revealed differences between influencer content and UGC. In influencer content, Behavioral Engagement is influenced by Homophily and Content Quality. On the other hand, in UGC, Behavioral Engagement is influenced by Social Media Interactions. The results of this research are expected to provide theoretical contributions and managerial implications in the field of digital marketing, particularly regarding the use of social media and its influence on consumer behavior.